Impact of Carbon Tax and Carbon Emission Trading on Wind Power in China: Based on the Evolutionary Game Theory - Sun, Chuyu; Wei, Jing; Zhao, Xiaoli; Yang, Fan (Frontiers in Energy Research, 2022)
Global climate problems caused by overuse of fossil energy need to be settled urgently. To solve global warming threatening human life and production, environmental control policies have been proposed as the mainstream ways in pushing the renewable energy development worldwide, such as carbon tax, carbon trading emissions trading, fiscal subsidies, and so forth. This study examines how carbon tax and carbon emissions trading policies could be coupled with subsidy policies to better promote renewable energy development. carbon emissions trading. The data comes from seven carbon emissions trading pilots from 2013 to 2017 in China. Based on the evolutionary game, the research simulates the onshore wind power investment to deeply explore the spontaneous evolution process. Taking carbon tax and carbon emissions trading policies into account, the two evolutionary game models are constructed under the context of fiscal subsidy policy respectively. The results shows that under the scenario of carbon trading and subsidy policy coordination, investors will vote for wind farms; under the scenario of the carbon tax and subsidies coordination, investors will pay the funds in coal-fired power generation. Besides, this is worth noting that excessive carbon tax may give rise to the shrinking of the power industry. Accordingly, it is suggested that the government should continue to implement the carbon emissions trading policy and maintain the free quota below 80%, the carbon emissions trading price above 120.02 yuan/ton.